(3QSGdI aj CbSGe GdeOs ((3CMeO QaYJ s)
(3ChdgG (B:s
(3EYde Cf GdeO jfbSe Ydi CQHYI YTQ bSekG GdChd eO GdMLR bhdg JYGdi (B( (3CfPQJge (B) (3CFPG jSei HPdc dONhd GdCda Hjf GdgeRJjf MGLRI HjfgeG Ci eHYOI CMOgeG Ydi GdCNQi YfO GdHYV s
(3BNQgG (B:s
(3GdKGdK YTQ eO GdYGQ GdeTOO fMh U b jS s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdbQGAGJ hGdJLhjOs